Variable structure control of manipulators with joints having flexibility and backlash - Machado, J. A. Tenreiro (2016)
This article studies the variable structure control of robot manipulators with joints having flexibility and bcklash. A second order reference model and smoth control law eliminate the reaching phase problems and the chattering usually present in the sliding mode. The results show a remarkable improvement of the stability over conventional variable structure controllers, while the algorithm maintains a low computational load that makes it well suited for microcomputer implementation.